2019
DOI: 10.2147/ndt.s196086
|View full text |Cite
|
Sign up to set email alerts
|

<p>Repetitive transcranial magnetic stimulation as an adjunctive treatment for negative symptoms and cognitive impairment in patients with schizophrenia: a randomized, double-blind, sham-controlled trial</p>

Abstract: Purpose: Effective treatment options for negative symptoms and cognitive impairment in patients with schizophrenia are still to be developed. The present study was to examine potential benefits of repetitive transcranial magnetic stimulation (rTMS) to improve negative symptoms and cognition in this patient population. Methods: The study was a 4-week, randomized, double-blind sham-controlled trial. Patients with schizophrenia were treated with adjunctive 20-Hz rTMS for 4 weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 42 publications
1
22
0
1
Order By: Relevance
“…We showed that dysbiosis of the gut microbiota could significantly affect the metabolic phenotypes of the cortex, cerebellum and striatum in schizophrenia microbiota recipient mice. Consistent with these findings, previous neuroimaging studies have shown that these regions are highly correlated with the onset of schizophrenia 2730. Additionally, at a functional level, alterations of lipid, amino acid and carbohydrate metabolism were also observed in schizophrenia microbiota recipient mice 16.…”
Section: Discussionsupporting
confidence: 84%
“…We showed that dysbiosis of the gut microbiota could significantly affect the metabolic phenotypes of the cortex, cerebellum and striatum in schizophrenia microbiota recipient mice. Consistent with these findings, previous neuroimaging studies have shown that these regions are highly correlated with the onset of schizophrenia 2730. Additionally, at a functional level, alterations of lipid, amino acid and carbohydrate metabolism were also observed in schizophrenia microbiota recipient mice 16.…”
Section: Discussionsupporting
confidence: 84%
“…Further, a recent study not only showed negative symptom improvement after 4 weeks of 10 Hz rTMS over the DLPFC, but this effect was maintained at the 24-week follow up (43). Most previous studies that treated schizophrenia patients with 20 Hz rTMS over the left DLPFC also showed significant improvements in negative symptoms (44)(45)(46). What we know is that higher frequencies of rTMS (frequencies of 5 Hz and greater) have been shown to have excitatory effects on neurons in the stimulated cortex (47).…”
Section: Discussionmentioning
confidence: 92%
“…In a neuroimaging study with perfusion SPECT on healthy people, 20 Hz rTMS targeted the left DLPFC region has been resulted in increased blood flow in dorsolateral prefrontal, anterior cingulate and orbitofrontal cortices ( George et al, 1999 ). With high frequency rTMS on DLPFC, although, some studies reported an improvement in selective attention ( Martis et al, 2003 ; Rektorova et al, 2005 ), some found no difference of cognitive functions ( Boggio et al, 2005 ; Huang et al, 2004 ; Zhuo et al, 2019 ). In another study, Barr et al have shown a significant improvement in working memory by applying bilateral 20 Hz rTMS on DLPFC sequentially ( Barr et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%